Proportion of Pneumoconiosis in Limestone Mining Workers In Citatah Village, West Bandung District - Widhy Yudistira Nalapraya; Agus Dwi Susanto; Mukhtar Ikhsan; Muchtarrudin Mansyur; Caecilia Marliana (Respiratory Science, 2021)
Background: Silica, asbestos and coal dust are associated with pneumoconiosis in mining workers. The International Labor Organization (ILO) reports that 30-50% of workers in developing countries are diagnosed with pneumoconiosis. This study aims to identify pneumoconiosis in limestone mining workers in Indonesia. Method: This cross-sectional study involved 73 subjects of limestone mining workers in Citatah Village, West Bandung Regency, Indonesia. Two conclusions were similar from three AIR-Pneumo certified photo readers by blind reading and using the ILO guidelines. Result: Pneumoconiosis was found in 11/73 (15.1%). The median age of the pneumoconiosis group was older than the non-pneumoconiosis group (51 [33-63] vs. 37.5 [18-85] age in years, p = 0.013). All subjects in the pneukoniosis group worked> 6 years (p = 0.001). The highest dust concentration was in the pneumoconiosis group compared to the non-pneumoconisosis group (61.41 ± 103.98 vs. 14.92 ± 55.17 mg / m3, p = 0.030). This study showed that the length of work and the level of dust in the mine were risk factors for pneumoconiosis, although not significant (OR = 14.6, p = 0.999 and OR = 7,171, p = 0.998). Conclusion: The proportion of pneumoconiosis in lime mining workers in this study was 15.1%. Length of work and dust levels in the mine are risk factors for pneumoconiosis; but not meaningful in this study.